The ERK-p38MAPK-STAT3 Signalling Axis Regulates iNOS Expression and Salmonella Infection in Senescent Cells - Fernandes, Sheryl Erica; Saini, Deepak Kumar (Frontiers in Cellular and Infection Microbiology, 2021)
The cellular changes occurring due to senescence like proliferation arrest, increase in free radical levels, and secretion of pro-inflammatory cytokines have been well studied, but its associated alteration in intracellular signalling networks has been scarcely explored. In this study, we examine the roles of three major kinases viz. p38 MAPK, ERK, and STAT3 in regulating iNOS expression and thereby the levels of the free radical Nitric oxide in senescent cells. Our study revealed that these kinases could differentially regulate iNOS in senescent cells compared to non-senescent cells. Further, we tested the physiological relevance of these alterations with Salmonella infection assays and established an inter-regulatory network between these kinases unique to infected senescent cells. Overall, our findings show how key signalling networks may be rewired in senescent cells rendering them phenotypically different.